Microstructural, Optical and Electrical Properties of ZnO: Pr Thin Films: Pr-Doping Level Effect - He, Hai-Yan (Micro and Nanosystems, 2016)
Background: ZnO is an important semiconductor transparent conductive material. The optical and electrical properties can be enhanced by some dopings. This work focus on the effect of Pr doping. Methods: A series of ZnO: Pr films with Pr contents of 0-2.0 at % were deposited by a chemical solution deposition. The deposited films were characterized by X-ray diffraction, field emission scanning electron microscopy, UV-vis and luminescent spectrophotometry, and electrical property measurement. Results: Pr-doping resulted in an obvious variation of optical transmittance in the UV-visible light range, band gap and electrical resistance. The film with a Pr content of 1.5 at.% showed optimal optical and electrical properties. The films also showed a strong band gap emission and two weak emissions related to intrinsic defects of ZnO and defects introduced by the Pr substitution. The emission intensity was related with Pr content. Some other optical parameters were also calculated based on the ultraviolet visible spectra. Conclusion: The optical and electrical properties of ZnO film can be enhanced by small amount of Pr doping. This is of significance to the optical and electrical applications of the Sm-doped ZnO materials.
Keywords: Electrical resistance